(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 00:18:54
(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方(-3a平方)平方+
(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方
(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方
(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方
(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方
=9a4次方+3a4次方+a4次方
=13a的4次方
(-3a平方)平方+(-3a)·(-a)立方+(-a)四次方
=(-3)平方*(a平方)平方+(-3)(a)·(-1)立方(a)立方+(-1)四次方(a)四次方
=9a四次方+3a四次方+a四次方
=13a四次方
3a平方+a平方-(2a平方-2a)+(3a-a平方)
计算:5a平方-[a平方+(5a平方-2a)-2(a平方-3a)]
(-3a立方)平方/a平方
(a-3)平方-(2a-b)平方
(3a平方-b平方)的平方-(a平方-3b平方)的平方 因式分解
3a平方-2a+4a平方-7a
(3a平方+2a-8)平方-(a平方-2a-8)平方
3a平方+【a平方-2a)-3(a平方-3a)]其中a=-2
-[-7a平方-5a+(2a平方-3a)+2a]-4a平方. 很急啊.
1/3a平方b立方·(-15a平方b平方)1/3a平方b立方乘(-15a平方b平方)
a平方b-[a平方b-(2abc-a平方c-3a平方b)-4a平方c]-abc
计算:5a平方-[a平方+(5a平方-2a)-2(a平方-3a)-4a]
若a平方+b平方+5=3(a平方+b平方)-3则a平方+b平方=
3a平方-2a+4a平方—a-5a平方—1=
-2a平方-2(5a平方+2a) +(3a平方-10a)计算
(-3a)平方乘以(2a平方-a-3)
3a-12a的平方+18a的平方
(a+3)的平方(a的平方+9)的平方(a-3)的平方